(untitled) (Philadelphia, 2001)
Sixty-four chapters, each written by a specialist in the field, use the question and answer format of this series to convey the material--in this instance, the important ideas and common poisons health care professionals might encounter in their practice--in an accessible, succinct fashion. The major topic divisions include: general principles, over-the-counter drugs, prescription medications, antibiotics, cardiac drugs, psychopharmacologic medications, drugs of abuse, metals, chemicals, pesticides, gases, food poisoning, botanicals, envenomations, and toxic terrorist threats. In addition, the authors have provided extra-credit trivia questions to enliven the subject and allow the reader "to bask in the center of attention at cocktail parties."
Keywords: Toxicology,Drugs,Toxicology; Miscellanea,Toxicology,Examination Questions; Miscellanea